Fluid Management in Pediatric Craniotomy - Fuadi, Iwan; Pison, Osmond Muvtilof; Redjeki, Ike Sri (Perdatin Pusat, 2015)
Advances in pediatric neurosurgery techniques have dramatically improved the outcome in infants and children with surgical lesions of the central nervous system. However, the physiologic and developmental differences inherent in pediatric patients present challenges to neurosurgeons and anesthesiologists alike. Fluid management is critically important in pediatric craniotomy. Hemodynamic stability during intracranial surgery requires the careful maintenance of intravascular volume and electrolytes. It is imperative to secure excellent intravenous access for fluid and blood replacement and drug delivery before the start of the operation. Lack of intake or active vomiting because of changes in the ICP, preoperative fluid restriction and diuretic therapy may lead to blood pressure instability and even cardiovascular collapse if sudden blood loss occurs. Normovolemia should be maintained throughout the procedure. Normal saline used as the maintenance fluid during neurosurgery because it’s mildly hyperosmolar and should minimize cerebral edema. Maintenance rate of fluid administration depends on the weight of the patient. The maximum allowable blood loss should be determined in advance. Hyperglycemia is always best avoided because it may exacerbate neurologic injury. Fluid management in neurosurgical cases is extremely important and requires good communication between the surgeon and anesthesiologist. Especially for infants and children because of the difference in the anatomy and physiology at various stages of growth and development. The anesthesiologist must be fully cognizant of these differences in order to conduct a safe anesthetic plan.